Induksi Mutasi Kromosom dengan Kolkisin pada Tanaman Anggur Merah (Vitis vinifera L. Varietas Prabu Bestari) Melalui Pembentukan Kalus Secara In Vitro - DIMINDA ELA SRI ERTINA BR GINTING; MADE SRITAMIN; WAYAN ADIARTAYASA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Induction of Chromosome Mutations with Colchicin in Red Grape (Vitis vinifera L. Prabu Bestari Varieties) Through In Vitro Callus Formation This study aims to determine the colchicine concentration that can induce chromosome mutations in red grape, carried out in vitro. This study used a completely randomized design (CRD) with 9 treatments and 3 replications so that the number of experimental units was 27 bottles of culture. The sterilized red grape node explants were immersed in colchicine at the concentration according to the treatment for 24 hours. The colchicine concentration used was 0.015% (K1), 0.020% (K2), 0.025% (K3), 0.030% (K4), 0.035% (K5), 0.040% (K6), 0.045% (K7), 0.050% ( K8) and 0% (K0) as controls. The effect of immersion in several colchicine concentrations on chromosome mutations in explants of red grape nodes that form callus cannot be observed because the chromosomes are not clearly visible, and the number of chromosomes cannot be calculated. Callus was formed in colchicine immersion treatment with a concentration of 0.015% (K1) and 0.035% (K5). Callus on K5 was formed faster, namely 10 weeks after planting, while K1 was at 11 weeks after planting. The average callus diameter on K5 was larger with a size of 4.3 mm, while on K1 it was 2 mm.